Utility of ERAS Pathway in Nonabdominal-Based Microsurgical Breast Reconstruction: Efficacy in PAP Flap Reconstruction? - Cho, Min-Jeong; Garza, Ricardo; Teotia, Sumeet S.; Haddock, Nicholas T. (Journal of Reconstructive Microsurgery, 2021)
Background Enhanced recovery after surgery (ERAS) protocols are effective in decreasing hospital length of stay and inpatient opioid consumption. Implementation of these protocols in abdominally based breast reconstruction has been successful. When a patient is a poor candidate for abdominally based flaps a popular secondary option is the profunda artery perforator (PAP) flap. We present our experience with implementation of our ERAS protocol in patients treated with PAP flaps for breast reconstruction.Methods Retrospective review of patients treated with autologous breast reconstruction using PAP flaps before and after ERAS implementation were performed. Patient characteristics, postoperative oral morphine equivalents (OMEs), and flap data were collected.Results A total of 87 patients were included in this study (58 patients in pre-ERAS and 29 patients in ERAS group). There was no statistical difference in patient age, comorbidities, smoking, and radiation between two groups. The ERAS group had statistically lower hospital length of stay (2.6 vs. 3.8 days), procedure time (315 vs. 433 minutes), postoperative day 0 (54.8 vs. 96.3), postoperative day 1 (29.9 vs. 57.7), and total opioid consumption (103.7 vs. 192.1). There was no statistical difference in average pain scores between two groups. Multivariate analysis revealed that procedure time significantly increased the amount of opioid consumption while ERAS implementation significantly reduced LOS and opioid consumption.Conclusion Use of an ERAS protocol in PAP flap breast reconstruction has not been previously studied. Our work shows that ERAS implementation in PAP flap breast reconstruction significantly reduces inpatient opioid use and length of hospital stay.
Keywords: ERAS; breast reconstruction; profunda artery perforator; opioid usage; length of hospital stay; DIEP